Tingkat Pengetahuan Tentang Stunting dan Wash (Water, Sanitation, Hygiene) Bagi Orang Tua di Sekitar TPA Bukit Pinang Kota Samarinda - Reni Suhelmi; A. Daramusseng; Julia Anggraeni; Olia Renata Audina (Abdimas Universal, 2022)
Stunting is one of the recent health issues in Samarinda city. The result of research showed that 32,5% of children has experienced stunting in around Bukit Pinang final disposal in 2020. Stunting were caused by various factor, such us environmental factors water, sanitation and hygiene (WASH). Based on the data, it needed intervention activity such us education  about stunting and WASH. The activity aimed to analyze the level of knowledge about stunting and WASH. The method of this activity through discussion and pre-post test questionnaire. The result of data analysy reported that there was the significant difference between before and after education abaut stunting (p = 0.032) and WASH (p = 0.008). It recommend to continue the education activities due to analyse the level of behavior about this project.